Intercomparison of direct sampling methods of volcanic gases and implications for the determination of chlorine isotopic compositions in fumaroles - E. Le Glas; M. Bonifacie; F. Tassi; G. Bardoux; R. Moretti; V. Robert; E. Chilin-Eusebe; H. Balcone-Boissard; P. Agrinier (Journal of Volcanology and Geothermal Research, 2026)

Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

The global role of bioassessment in policy delivery and decision-making for inland waters - Martyn G. Kelly; Gary Free; John P. Simaika; Stuart Warner; Andreas Bruder; Alejandra Correa-Bedoya; Fabio de Oliveira Roque; Tor Erik Eriksen; Jennifer Lento; Craig R. Macadam; Kristian Meissner; Marcelo S. Moretti; et al. (Journal of Environmental Management, 2025)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Correction to: The European Volcano Observatories and their use of the aviation colour code system - Sara Barsotti; Simona Scollo; Giovanni Macedonio; Alicia Felpeto; Aline Peltier; Georgios Vougioukalakis; Elske de Zeeuw van Dalfsen; Lars Ottemöller; Adriano Pimentel; Jean-Christophe Komorowski; Susan Loughlin; Rita Carmo; et al. (Bulletin of Volcanology, 2024)

The rheological response of magma to nanolitisation - Luiz Pereira; Yannick Linard; Fabian B. Wadsworth; Jérémie Vasseur; Kai-Uwe Hess; Roberto Moretti; Donald B. Dingwell; Daniel R. Neuville (Journal of Volcanology and Geothermal Research, 2024)

The European Volcano Observatories and their use of the aviation colour code system - Sara Barsotti; Simona Scollo; Giovanni Macedonio; Alicia Felpeto; Aline Peltier; Georgios Vougioukalakis; Elske de Zeeuw van Dalfsen; Lars Ottemöller; Adriano Pimentel; Jean-Christophe Komorowski; Susan Loughlin; Rita Carmo; et al. (Bulletin of Volcanology, 2024)
Volcano observatories (VOs) around the world are required to maintain surveillance of their volcanoes and inform civil protection and aviation authorities about impending eruptions. They often work through consolidated procedures to respond to volcanic crises in a timely manner and provide a service to the community aimed at reducing the potential impact of an eruption. Within the International Airways Volcano Watch (IAVW) framework of the International Civil Aviation Organisation (ICAO), designated State Volcano Observatories (SVOs) are asked to operate a colour coded system designed to inform the aviation community about the status of a volcano and the expected threats associated. Despite the IAVW documentation defining the different colour-coded levels, operating the aviation colour code in a standardised way is not easy, as sometimes, different SVOs adopt different strategies on how, when, and why to change it. Following two European VOs and Volcanic Ash Advisory Centres (VAACs) workshops, the European VOs agreed to present an overview on how they operate the aviation colour code. The comparative analysis presented here reveals that not all VOs in Europe use this system as part of their operational response, mainly because of a lack of volcanic eruptions since the aviation colour code was officially established, or the absence of a formal designation as an SVO. We also note that the VOs that do regularly use aviation colour code operate it differently depending on the frequency and styles of eruptions, the historical eruptive activity, the nature of the unrest, the monitoring level, institutional norms, previous experiences, and on the agreement they may have with the local Air Transport Navigation providers. This study shows that even though the aviation colour code system was designed to provide a standard, its usage strongly depends on the institutional subjectivity in responding to volcano emergencies. Some common questions have been identified across the different (S)VOs that will need to be addressed by ICAO to have a more harmonised approach and usage of the aviation colour code.

Towards harmonized standards for freshwater biodiversity monitoring and biological assessment using benthic macroinvertebrates - John P. Simaika; James Stribling; Jennifer Lento; Andreas Bruder; Sandra Poikane; Marcelo S. Moretti; Nick Rivers-Moore; Kristian Meissner; Craig R. Macadam (Science of The Total Environment, 2024)

Allele and genotype frequencies for primary hereditary cataract, multifocal retinopathy 1, and degenerative myelopathy in Pyrenean Mountain dog from Italy - R. Moretti; G. Massimello; S. Chessa; S. Sartore; A. Tranchero; M. Profiti; P. Sacchi (Topics in Companion Animal Medicine, 2024)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

Diverse magma storage and major and volatile magma composition: What are the implications on the eruptive style across a volcanic arc? An example of the Lesser Antilles Arc - A. Metcalfe; S. Moune; J.-C. Komorowski; R. Robertson; T.E. Christopher; E.P. Joseph; R. Moretti (Earth-Science Reviews, 2023)

Sedimentological features of asbestos cement fragments in coastal environments (Taranto, southern Italy) - S. Lisco; I. Lapietra; R. Laviano; G. Mastronuzzi; T. Fracchiolla; M. Moretti (Marine Pollution Bulletin, 2023)

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Whole-rock oxygen isotope ratios as a proxy for the strength and stiffness of hydrothermally altered volcanic rocks - Michael J. Heap; Valentin R. Troll; Chris Harris; H. Albert Gilg; Roberto Moretti; Marina Rosas-Carbajal; Jean-Christophe Komorowski; Patrick Baud (Bulletin of Volcanology, 2022)

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Effects of Maternal Dietary Cottonseed on the Profile of Minerals in the Testes of the Lamb - Helder Louvandini; Egon H. Ieda; Carolina R. Jimenez; Patricia Spoto Corrêa; Debora B. Moretti; Paulo M. T. Lima; Concepta M. McManus; Hudson W. P. Carvalho; Elisabete A. De N. Fernandes (Biological Trace Element Research, 2020)

In situ XANES study of the influence of varying temperature and oxygen fugacity on iron oxidation state and coordination in a phonolitic melt - Charles Le Losq; Roberto Moretti; Clive Oppenheimer; François Baudelet; Daniel R. Neuville (Contributions to Mineralogy and Petrology, 2020)

A preliminary investigation of corpus callosum subregion white matter vulnerability and relation to chronic outcome in boxers - Ashley L. Ware; Elisabeth A. Wilde; Mary R. Newsome; Paolo Moretti; Tracy Abildskov; Gregory S. Vogt; Stephen R. McCauley; Gerri Hanten; Jill V. Hunter; Zili D. Chu; Harvey S. Levin (Brain Imaging and Behavior, 2020)

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Multisource data integration to investigate one century of evolution for the Agnone landslide (Molise, southern Italy) - M. Del Soldato; A. Riquelme; S. Bianchini; R. Tomàs; D. Di Martire; P. De Vita; S. Moretti; D. Calcaterra (Landslides, 2018)

Claviceps arundinis identification and its role in the die-back syndrome of Phragmites australis populations in central Italy - M. Cerri; L. Reale; C. Moretti; R. Buonaurio; A. Coppi; V. Ferri; B. Foggi; D. Gigante; L. Lastrucci; M. Quaglia; R. Venanzoni; F. Ferranti (Plant Biosystems, 2018)

Incorporation of 5-ethynyl-2′-deoxyuridine (EdU) as a novel strategy for identification of the skewed X inactivation pattern in balanced and unbalanced X-rearrangements - Luiza Sisdelli; Angela Cristina Vidi; Mariana Moysés-Oliveira; Adriana Di Battista; Adriana Bortolai; Danilo Moretti-Ferreira; Magnus R. Dias da Silva; Maria Isabel Melaragno; Gianna Carvalheira (Human Genetics, 2016)

Ant community in natural fragments of the Brazilian wetland: species–area relation and isolation - Rafael G. Cuissi; Chaim J. Lasmar; Tamara S. Moretti; Fernando A. Schmidt; Wedson D. Fernandes; Andreia B. Falleiros; José H. Schoereder; Carla R. Ribas (Journal of Insect Conservation, 2015)

Geochemical and isotopic insights into the assembly, evolution and disruption of a magmatic plumbing system before and after a cataclysmic caldera-collapse eruption at Ischia volcano (Italy) - R. J. Brown; L. Civetta; I. Arienzo; M. D’Antonio; R. Moretti; G. Orsi; E. L. Tomlinson; P. G. Albert; M. A. Menzies (Contributions to Mineralogy and Petrology, 2014)

High-Resolution Fibre-Optic Temperature Sensing: A New Tool to Study the Two-Dimensional Structure of Atmospheric Surface-Layer Flow - Christoph K. Thomas; Adam M. Kennedy; John S. Selker; Ayla Moretti; Martin H. Schroth; Alexander R. Smoot; Nicholas B. Tufillaro; Matthias J. Zeeman (Boundary-Layer Meteorology, 2012)

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Anti-HIV Drugs Nevirapine and Efavirenz Affect Anxiety-Related Behavior and Cognitive Performance in Mice - Pedro R. T. Romão; Joelson C. Lemos; Jeverson Moreira; Gisele de Chaves; Morgana Moretti; Adalberto A. Castro; Vanessa M. Andrade; Carina R. Boeck; João Quevedo; Elaine C. Gavioli (Neurotoxicity Research, 2011)

Spider, bee, and bird communities in cities are shaped by environmental control and high stochasticity - T. Sattler; D. Borcard; R. Arlettaz; F. Bontadina; P. Legendre; M. K. Obrist; M. Moretti (Ecology, 2010)
Spatially organized distribution patterns of species and communities are shaped by both autogenic processes (neutral mechanism theory) and exogenous processes (niche theory). In the latter, environmental variables that are themselves spatially organized induce spatial structure in the response variables. The relative importance of these processes has not yet been investigated in urban habitats. We compared the variance explained by purely spatial, spatially structured environmental, and purely environmental components for the community composition of spiders (Araneae), bees (Apidae), and birds (Aves) at 96 locations in three Swiss cities. Environmental variables (topography, climate, land cover, urban green management) were measured on four different radii around sampling points ( Our results suggest that the anthropogenic structuring of urban areas has disrupted the spatial organization of environmental variables and inhibited the development of biotic spatial processes. The near absence of spatial structure may therefore be a feature typical of urban species assemblages, resulting in urban community composition mainly influenced by local environmental variables. Urban environments represent a close‐knit mosaic of habitats that are regularly disturbed. Species communities in urban areas are far from equilibrium. Our analysis also suggests that urban communities need to be considered as being in constant change to adapt to disturbances and changes imposed by human activities.

Blockade of adenosine A2A receptor counteracts neuropeptide-S-induced hyperlocomotion in mice - Carina R. Boeck; Caroline Martinello; Adalberto A. de Castro; Morgana Moretti; Tiago dos Santos Casagrande; Remo Guerrini; Girolamo Calo’; Elaine C. Gavioli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Dominance of Group 2 and fusaproliferin production by Fusarium subglutinans from Iowa maize - G.P. Munkvold; A. Logrieco; A. Moretti; R. Ferracane; A. Ritieni (Food Additives & Contaminants: Part A, 2009)

Identification of severe potential drug-drug interactions using an Italian general-practitioner database - L. Magro; A. Conforti; F. Del Zotti; R. Leone; M. L. Iorio; I. Meneghelli; D. Massignani; E. Visonà; U. Moretti (European Journal of Clinical Pharmacology, 2008)

Viral outcome of simian–human immunodeficiency virus SHIV-89.6P adapted to cynomolgus monkeys - A. Borsetti; S. Baroncelli; M. T. Maggiorella; S. Bellino; S. Moretti; L. Sernicola; R. Belli; B. Ridolfi; S. Farcomeni; D. R. M. Negri; A. Cafaro; B. Ensoli; et al. (Archives of Virology, 2008)

Potential role of SEN virus on liver enzyme abnormalities in patients positive for hepatitis C virus with or without HIV infection - E. Quiros-Roldan; F. Moretti; C. Torti; V. Tirelli; R. Stellini; S. Pirovano; G. Carosi; L. Imberti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Nimesulide and renal impairment - R. Leone; A. Conforti; E. Ghiotto; U. Moretti; E. Valvo; G. P. Velo (European Journal of Clinical Pharmacology, 1999)

Applicability of Aspecific Noninvasive Methods for Biomonitoring of Occupational Exposure to Deltamethrin: Preliminary Study Using an Animal Model - M. Moretti; M. Villarini; G. Scassellati-Sforzolini; R. Pasquini; S. Monarca (Archives of Environmental Contamination and Toxicology, 1997)